Health Seeking Behaviour among Persons with STIs in Ghana - Sawyerr, R.T. (University of Ghana, 2019)
Over the years, the meaning of health seeking behaviour (HSB) has gone beyond just the use of health care facilities to include understanding what social and cultural factors influence a person’s decision to utilize a healthcare facility. Although most STIs are treatable, a range of social and cultural factors prevent access to healthcare treatment and this contributes to the burden of untreated infection. An important tool in effective sexually transmitted infection (STI) control is to understand the health seeking behaviour of people with STIs and the factors that influence this behaviour. Although data on STI prevalence in Ghana is accessible, studies on health seeking behaviour with regards to individuals with STIs is limited. This study aims to examine the demographic and socio-economic determinants of the health seeking behaviour of persons with STIs in Ghana using data from the 2014 Ghana Demographic and Health Survey (GDHS). A sample of 1974 females and 307 males between the ages of 15-49 years was used in this study. Analyses were carried out at three levels; univariate, bivariate and multivariate levels of analyses. Univariate analysis was used to provide a description of the background characteristics of the sample population. Chi-square tests were used to test for associations between the independent and dependent variables as well as the intermediate and dependent variables while binary logistic regression tests were used to determine predictors at a 95% confidence level. Findings showed that 70.2% of respondents sought STI treatment. Results from the bivariate analysis revealed that age, place of residence, ethnicity, educational level, region of residence, religion, wealth quintile, knowledge about STIs, health insurance were found to have a significant relationship with health seeking behaviour. However, sex, marital status and employment status were not statistically significant with health seeking behaviour. This study brought to the fore the fact that even though the majority of respondents sought STI treatment, teenagers, individuals with lower levels of education, poorer individuals, traditionalists, individuals with no health insurance and individuals with poor knowledge about STIs had lesser likelihoods of seeking STI treatment. This implies that age, education, wealth, religion, health insurance and knowledge about STIs are predictors of health seeking behaviour in Ghana. This study therefore recommends that, the sub-groups less likely to seek STI treatment need to be targeted during policy formulation to improve health seeking behaviour and subsequently sexual and reproductive health. Key words: Health Seeking Behaviour, Sexually Transmitted Infection, Demographic and Socioeconomic Determinants, Ghana
MA. Population Studies
Keywords: Health Seeking Behaviour; Sexually Transmitted Infection; Ghana